An assessment of the olive ridley turtle ( Lepidochelys olivacea) nesting population in Orissa, India - Shanker, Kartik; Pandav, Bivash; Choudhury, B.C. (Biological conservation, 2004)
Olive ridley mass nesting events or ‘ arribadas’ have been documented in Orissa, India since 1974. However, since standardised techniques have not been used to census turtles, actual population trends remain unknown. Herein, we summarise information on nesting populations in Orissa, using data from multiple sources to arrive at consensus estimates and to derive trends. We conducted a quantitative estimate of an arribada in March 1999, where nesting was estimated as ∼180,000 turtles by the strip transect method. Non-linear (quadratic) fits for arribada data from 1976–1999 and a recent decrease in the size of adults suggest a potential or imminent decline, consistent with fishery-related mortality of at least 90,000 turtles since 1994. Though statistical support for the recent decline is equivocal, efforts to reduce mortality and close monitoring of the population would be prudent. The absence of reliable data on which to base conservation action highlights an urgent need to train management personnel in data collection and estimation techniques for effective monitoring of status, threats and trends.